BYUDJETDAN TASHQARI MAQSADLI JAMG‘ARMALARNING IQTISODIY MOHIYATI VA NAZARIY KONSEPSIYALARI - Nurmatov Baxodir Abdurapiyevich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
In recent years, the importance of extra-budgetary targeted funds within the public financial management system has been steadily increasing. This is primarily because the state budget alone cannot fully cover the financing needs of all socio-economic projects. Therefore, in order to mobilize additional financial resources and ensure both social protection and economic development, special funds are established. These funds function not only as supplementary financial sources but also as crucial instruments for implementing state financial policy. Extra-budgetary funds represent financial resources established for the fulfillment of specific socio-economic objectives, operating outside the state budget. Their distinctive feature lies in maintaining independent accounts of revenues and expenditures. Although they do not formally enter the state budget, they remain an integral component of the national financial system. Through such funds, the government redistributes a portion of national income to targeted segments of the population in line with social needs. At the same time, these funds play a significant role in financing strategic initiatives in priority areas of state policy.